2011
DOI: 10.1053/j.gastro.2010.09.042
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Control of HCV Is Associated With Expression of HLA-B*57 and Preservation of Targeted Epitopes

Abstract: Background and Aims HLA Class I alleles are linked to spontaneous control of HCV and HIV-1, but for HCV the roles of particular alleles and corresponding CD8+ T-cell responses remain incompletely defined. We aimed to determine the correlations between these alleles and natural outcome of HCV and determine associated key T cell responses. Methods In a cohort of HCV individuals we determined HLA Class I alleles, HCV outcome, T-cell responses, and examined sequence data for mutational changes within key epitope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
147
2
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 132 publications
(158 citation statements)
references
References 32 publications
8
147
2
1
Order By: Relevance
“…Preponderance of sector 1 sites in the NS3 epitopes targeted by HCV controllers. Clinical studies of HCV-infected cohorts have shown that possession of specific HLA alleles is highly correlated with the ability to spontaneously clear HCV by immunemediated mechanisms (24,(51)(52)(53)(54)(55). In this work, we studied two classes of protective epitopes to validate our findings.…”
Section: Resultsmentioning
confidence: 63%
“…Preponderance of sector 1 sites in the NS3 epitopes targeted by HCV controllers. Clinical studies of HCV-infected cohorts have shown that possession of specific HLA alleles is highly correlated with the ability to spontaneously clear HCV by immunemediated mechanisms (24,(51)(52)(53)(54)(55). In this work, we studied two classes of protective epitopes to validate our findings.…”
Section: Resultsmentioning
confidence: 63%
“…Alleles such as HLA-A*03, HLA-B*27, and HLA-B*57 have been described to be associated with spontaneous resolution of HCV infection (21,27,49). It has been highlighted that these "protective" HLA class I alleles highly reproducibly select for escape mutations in the corresponding immunodominant epitopes (21,29,33). A study of the mechanisms of protection by HLA-B*27 pointed out that a rather complex pattern of 2, or sometimes even 3, substitutions is selected (8).…”
Section: Discussionmentioning
confidence: 99%
“…The CD8 ϩ T cell response against the epitope IPFYGKAI 1373-1380 was also studied in a patient with acute HCV genotype 1a infection. The patient was previously reported in a study on the impact of HLA-B*57 on HCV infection outcome (30) and was also HLA-B*51 positive. Interestingly, here, the response was detectable by week 11 after infection but became completely undetectable in an IFN-␥ enzyme-linked immunospot (ELISpot) assay by week 47 (Fig.…”
Section: Cd8mentioning
confidence: 85%